Open arms, conflicted hearts: nurse‐practitioner's attitudes towards working with lesbian, gay and bisexual patients. Issue 23 (December 2016) - Dorsen, Caroline; Van Devanter, Nancy
Abstract : Aims and Objectives: To explore nurse‐practitioner's attitudes towards working with lesbian, gay and bisexual patients. Background: Literature suggests that lesbians, gay men and bisexuals have significant health disparities compared to heterosexuals. Although the reasons are multifactorial, research suggests that attitudes of healthcare providers (HCPs) may be a contributing factor in both accessing and receiving care. There is currently no literature exploring the attitudes of the approximately 300, 000 nurse‐practitioners in the United States. Thus, nurse‐practitioners strengths and challenges in providing care to sexual minorities are unknown. Design: As part of a larger study, Corbin & Strauss' grounded theory methodology was used to explore the attitudes towards lesbian, gay and bisexual patients among primary care nurse‐practitioners in NYC. Methods: Data were collected via individual semi‐structured interviews with nurse‐practitioners currently in practice in primary or outpatient care in NYC ( n = 19). Data were evaluated using the three‐step constant comparison method. Results: Nurse‐practitioners in this study had varied, often overlapping and sometimes conflicting, attitudes about working with lesbian, gay and bisexual patients. The main theme identified was 'open arms, conflicted hearts' with three major subthemes – feeling at home, struggling to maintain professionalism and finding comfort under the umbrella of diversity. Conclusions: Nurse‐practitioner participants in this study had varied attitudes about working with lesbian, gay and bisexual patients, ranging from open, confident and comfortable to ambivalent, cautious and unsure about working with lesbian, gay and bisexual patients generally and specifically regarding the health needs of this population. Relevance to clinical practice: This study highlights the inadequate didactic and clinical preparation most nurse‐practitioners feel they have to care for lesbian, gay and bisexual patients. There is a need for increased education for registered nurses and nurse‐practitioners regarding lesbian, gay and bisexual culture, their unique healthcare needs, as well as the role of stigma and marginalisation in caring for vulnerable populations.